The influence of processing of lupins and canola on apparent metabolizable energy and broiler performance. - Breytenbach, Liesl (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MscAgric (Animal Sciences))--University of Stellenbosch, 2005.